Ճարտասանության խնդիրները Դիոնիսիոս Թրակացու քերականության հայկական մեկնություններում - Գառնիկ Անանյան (ՀՀ ԳԱԱ հրատ.)
Необходимость укрепления христианства в значительной степени возвысила значение речи (устной и письменной). "Человек в триединстве совершенен: душой, телом и словом, и если одно из них отсутствует — несовершенен человек",— резюмирует Вардан Вардапет (XIII в.). На первый план выступают методы усовершенствования устной и письменной речи. The necessity to strenghten the Christianity increased greatly the importance of the speech (oral and written). A person is perfect with three things: spirit, body and speech. If one of these lacks, the man appears to be imperfect, Vardan Vardapet (the 13th century) generalizes.
Keywords: B Philosophy; Psychology; Religion; Philology; Linguistics; Language and Literature; BR Christianity